Il secolo archeologico (Materiali di Estetica. Terza serie, 2021)
The twentieth century is characterized by a particular transformation in Architecture. It moves away from its own secular logic based on the recognizability and identity of the constituent elements and becomes the result of an intellectual process built on archaeological logic, the Foucauldian discourse on the aforementioned. From the beginning to the end of the century, with different characteristics and results, it is possible to identify this matrix in the different dominant thoughts in the architecture either conceived and built.
Keywords: Archaeology; Modern Movement; Postmodern; Supermodern